Hepatitis B virus X protein enhances the development of liver fibrosis and the expression of genes associated with epithelial-mesenchymal transitions and tumor progenitor cells. (7th June 2019) - Ahodantin, James; Lekbaby, Bouchra; Bou Nader, Myriam; Soussan, Patrick; Kremsdorf, Dina
Abstract: The hepatitis B virus X protein (HBx) has pleiotropic biological effects, which underlies its potential role in cell transformation. However, its involvement in hepatic fibrosis remains unclear. In this study, we wanted to clarify, in vivo, the role of HBx protein in the development of liver fibrosis. Mice transgenic for the full-length HBx (FL-HBx) were used. To create liver fibrosis, FL-HBx transgenic and control mice were chronically exposed to carbon tetrachloride (CCl4 ). Modulation of the expression of proteins involved in matrix remodeling, hepatic metabolism and epithelial-mesenchymal transition (EMT) were investigated. In transgenic mice, FL-HBx expression potentiates CCl4 -induced liver fibrosis with increased expression of proteins involved in matrix remodeling (Collagen1a, α-Sma, PdgfR-β, MMP-13). In FL-HBx transgenic mice, an increase in EMT was observed with a higher transcription of two inflammatory cytokines (TNF-α and TGF-β) and a decrease of glutamine synthetase expression level. This was associated with a sustained cell cycle and hepatocyte polyploidy alteration consistent with p38 and ERK1/2 overactivation, increase of PLK1 transcription, accumulation of SQSTM1/p62 protein and increase expression of Beclin-1. This correlates with a higher expression of tumor progenitor cell markers (AFP, Ly6D and EpCam), indicating a higher risk of progression from fibrosis to hepatocellular carcinoma (HCC) in the presence of FL-HBx protein. In conclusion, our results show that FL-HBx protein enhances the development of liver fibrosis and contributes to the progression of liver disease from chronic hepatitis to HCC.